Tracing Historical Footsteps: Digitalizing Javanese Tafsīr Manuscript as a Pedagogical Resource for Contextual Islamic Education - Ulfah Rahmawati; Aziizatul Khusniyah; Sholihah Sholihah; M Khusnu Zain; Ika Nur Fitriani (Indonesian Journal of Islamic Education Studies (IJIES), 2026)
Javanese-language Quranic exegesis manuscripts written in the Arabic-Pegon script represent an intellectual heritage of Islam in Indonesia; however, their use in Islamic Religious Education (IRE) remains limited due to challenges regarding readability, accessibility, and pedagogical integration. This study aims to analyze the characteristics of manuscripts LSM 011 and LSM 012 and to explore the transformation of their digitized versions into learning resources for the sub-topic "The Authenticity of the Qur'an." A qualitative approach was employed using a case study design integrated into a Research and Development (R&D) framework based on the ADDIE model. Data were gathered through manuscript observation, semi-structured interviews with philologists and manuscript collectors, philological analysis, and classroom observations during the module implementation phase. The results indicate that both manuscripts utilize the Javanese language in Arabic-Pegon script, employing the interlinear translation pattern. Digitization yielded four key transformations: manuscript preservation, enhanced accessibility, improved readability, and the integration of manuscript content into the IRE module. Classroom observations revealed that the module fostered student engagement and comprehension by leveraging familiar linguistic and cultural contexts. These findings underscore digitization as a process that encompasses both preservation and pedagogical transformation. Consequently, local manuscripts can be developed into accessible, contextually relevant PAI learning resources. The study contributes by expanding the function of digitization from mere preservation to pedagogical application rooted in local cultural heritage.